Arbuscular mycorrhizal and ectomycorrhizal plants together shape seedling diversity in a subtropical forest - Chen, Zhaoquan; Liu, Wande; Lang, Xuedong; Wang, Minghui; Liu, Jiao; Xu, Chonghua (Frontiers in Forests and Global Change, 2024)
Burgeoning mycorrhizal research has focused on identifying the various diverse mycorrhizal strategies of forest communities. Mounting evidence suggests that mycorrhizae play important roles in regulating forest community structure and composition. However, research into the manifestation of this influence in the seedling stage is lacking, especially in small-scale plots. Our research utilized structural equation models parameterized using data from a subtropical monsoon broad-leaved evergreen forest situated in Yunnan Province, China. We noted that seedlings included plants that utilized both arbuscular mycorrhizal (AM) and ectomycorrhizal (EM) fungi. More seedling plots with the relatively higher species diversity were the product of the mixed mycorrhizal strategy, meaning the coexistence of AM and EM seedlings in a small-scale plot rather than the dominance of one type of strategies. These mixed communities were primarily found on slopes and mountain ridges. The abundance of AM or EM trees indirectly affected seedling diversity by influencing the abundance of different mycorrhizal seedlings. In this case, the diversity of the mixed mycorrhizal community was also restricted by the level of leaf thickness in the community, followed by abiotic factors such as elevation, convexity, soil pH and soil available phosphorus. The effect of leaf thickness on mycorrhizal seedling abundance reflected the importance of water conditions in shaping seedling communities. The effect of convexity on seedling diversity also reflected the limitation of seedling communities by the distribution of humidity and heat conditions during topographic change.The results suggested that it is crucial to preserve seedling diversity via the mixed mycorrhizal strategy of communities in the subtropical forest.